2019
DOI: 10.3168/jds.2018-15348
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and nongenetic factors affecting on-farm performance of peri-urban dairy cattle in west Africa

Abstract: Population growth and urbanization lead to an increasing demand for milk in sub-Saharan Africa, but the production potential of the 65.9 million dairy cows in the region is far from being fully exploited to meet this demand. With the aim to support decision-making for breeding and management of dairy cattle in commercial farms, we performed a comparative study of daily milk offtake, chemical composition of milk, prevalence of metabolic disorders, and body weight development of local and crossbred cattle genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
(40 reference statements)
1
7
0
Order By: Relevance
“…In general, cows with the highest rank had higher body weights than poor cows, and Sahelian cows were heavier than Fulani zebu cows but lighter than taurine crossbred cows. This is in accordance with Roessler et al [11] who concluded that the body weight and growth rate of dairy cattle in peri-/urban farms in Ouagadougou were higher in imported cattle breeds than in the local Fulani cattle.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In general, cows with the highest rank had higher body weights than poor cows, and Sahelian cows were heavier than Fulani zebu cows but lighter than taurine crossbred cows. This is in accordance with Roessler et al [11] who concluded that the body weight and growth rate of dairy cattle in peri-/urban farms in Ouagadougou were higher in imported cattle breeds than in the local Fulani cattle.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, the milk yield was the most commonly used trait for the ranking of Sahelian zebu and taurine crossbred cows, and cows which were highly ranked had a higher reported milk yield than poor quality cows. The recorded milk offtake from taurine x Fulani zebu cows over a 16-month period in peri-/urban farms of Ouagadougou was four times higher than that from purebred Fulani zebu cows [11], while the reported amounts of extracted milk from taurine crossbred cows surpassed those of Fulani cows six fold in the present study. Furthermore, taurine crossbred cows were ranked as poor because of poor reproductive performance, although the overall comparison of the age at first calving and the calving interval did not reveal a difference between the ranks of the cows.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Limited involvement of farmers when designing crossbreeding programs, shortfalls of crossbreeding programs, inadequate funding of crossbreeding programs, environment and genotype mismatch, trained manpower problem were the major challenges facing smallholder dairy cattle crossbreeding in the tropics (Ojango et al, 2017). Additionally, genetic potential of crossbred cows is not fully exploited due to extreme climatic conditions and variable quantity and quality of feed resources in SSA (Roessler et al, 2019). Therefore, strategies designed to develop the dairy sector should take into account the existing production system and its unique characteristics of the area and should focus on a systematic approach to alleviate the identified constraints by involving all stakeholders in the formulation and implementation of improvement strategies (Moges, 2012;Ojango et al, 2017).…”
Section: Challenges Of Crossbreedingmentioning
confidence: 99%